Lo ‘sbattezzo’, tra libertà religiosa e norme implicite. Spunti di diritto comparato (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Considerazioni introduttive - 2. Il quadro normativo - 3. Le soluzioni giurisprudenziali - 4. Riflessioni conclusive.The ‘debaptism’, between religious freedom and implicit rules. Hints of comparative lawABSTRACT: The problem of cancellation from baptismal registers seems to have come to a final solution, thus being no more interesting. Nonetheless, it can still be useful to analyse it from a comparative point of view. The study of the various solutions proposed by the different legal systems allows finding out ‘implicit’ juridical principles, which condition the interpretation and the implementation of positive rules. It can be especially remarked a convergence of arguments and results between legal systems formally inspired to distinct models of State-religions’ relationship - such as the French and the Italian legal systems. This convergence highlights the existence, at a latent level, of common cultural conceptions of the religious experience, fashioned by the Christian religious paradigm; these conceptions tend to shape the concrete contents of both the right to religious freedom, and the right to personal identity, protected by personal data laws.
Keywords: Riservatezza